A metodologia da sala de recursos multifuncionais para a educação linguística dos surdos : um estudo bakhtiniano - Souza, Sebastiana Almeida (2014)
This study aims to demonstrate, in the light of theories which will be made explicit, how the methodologies applied in the Multifunctional Resource Room of EMEB Maria Dimpina Lobo Duarte, in Cuiabá-MT, contributed to the linguistic development process of deaf students in the classroom. Given this, we draw the following objectives: 1) To understand how the teachers of the MRR develop and apply the 03 didactic and pedagogical moments in the education of the deaf, and which are the contributions of these to learning in the classroom; 2) To understand how is the interaction between students and teachers in this teaching-learning process. To this end, we selected two research questions: What are the methodologies developed in the 03 didactic-pedagogical moments applied by the teachers of the MRR in teaching of deaf students in EMEB Maria Dimpina? How does the interactional process between teacher and student happen, and how this affects the teaching-learning process in the context of the MRR? We developed in our work, a qualitative research grounded in the Bakhtinian studies on language (BAKHTIN/VOLOSHINOV, 1929; BAKHTIN, 1952-1953). So we could anchor our methodology, we followed the considerations of Methodology of Human Sciences with Bakhtin (2006) and Amorim (2001); for the analysis of the pedagogical practices of teachers of the MRR, we used, essentially, the socio-historical learning theory of Vygotsky (1930), with emphasis on the concept Zone of Proximal Development. Information from observation of 08 lessons were used to generate the data; interviews with the people involved, as well as audio and video footage. Data analysis was performed focusing on some categories based on the theoretical framework described, based on Dialogical Analysis of Discourse, designed by Brait (2006). The results of our research, in terms of observation and analysis, showed that the deployment of these 03 didactic-pedagogical moments in the MRR: Specialized Educational Support Services for the Education in LIBRAS; Specialized Educational Support Services for the Education of LIBRAS and Specialized Education in Portuguese are important and necessary for the deaf student, since the knowledge developed there contributes to the fulfillment of their learning in the classroom.